Extracellular Vesicles and MicroRNA: Putative Role in Diagnosis and Treatment of Diabetic Retinopathy - Beatriz Martins; Madania Amorim; Flávio Reis; António Francisco Ambrósio; Rosa Fernandes (Antioxidants, 2020)
Diabetic retinopathy (DR) is a complex, progressive, and heterogenous retinal degenerative disease associated with diabetes duration. It is characterized by glial, neural, and microvascular dysfunction, being the blood-retinal barrier (BRB) breakdown a hallmark of the early stages. In advanced stages, there is formation of new blood vessels, which are fragile and prone to leaking. This disease, if left untreated, may result in severe vision loss and eventually legal blindness. Although there are some available treatment options for DR, most of them are targeted to the advanced stages of the disease, have some adverse effects, and many patients do not adequately respond to the treatment, which demands further research. Oxidative stress and low-grade inflammation are closely associated processes that play a critical role in the development of DR. Retinal cells communicate with each other or with another one, using cell junctions, adhesion contacts, and secreted soluble factors that can act in neighboring or long-distance cells. Another mechanism of cell communication is via secreted extracellular vesicles (EVs), through exchange of material. Here, we review the current knowledge on deregulation of cell-to-cell communication through EVs, discussing the changes in miRNA expression profiling in body fluids and their role in the development of DR. Thereafter, current and promising therapeutic agents for preventing the progression of DR will be discussed.